Label-Free Colorimetric Detection of Influenza Antigen Based on an Antibody-Polydiacetylene Conjugate and Its Coated Polyvinylidene Difluoride Membrane - Jeong, Jae-pil (Polymers (Basel), 2017)
This study presents an antibody-conjugated polydiacetylene (PDA) and its coated polyvinylidene difluoride (PVDF) membrane. The M149 antibody was hybridized to nano-vesicles consisting of pentacosa-10,12-diynoic acid (PCDA) and dimyristoylphosphatidylcholine (DMPC). After photo-polymerization at 254 nm, the effects on the PDA by antigenic injection were investigated with UV-vis spectroscopy, fluorescence spectroscopy, dynamic light scattering and transmission electron microscopy. Because PDA, an alternating ene-yne molecule, induces a blue-to-red color transition and an interesting fluorescent response by the distortion of its backbone, the biomolecular recognition of an antibody–antigen can be converted into an optical and fluorescent signal. Thus, an influenza antigen was successfully detected with the proposed label-free method. Furthermore, the vesicular system was improved by coating it onto a membrane type sensing platform for its stability and portability. The proposed antibody-PDA composite PVDF membrane has potential for rapid, easy and selective visualization of the influenza virus.